ANALISIS KESIAPAN PERANGKAT KAMPUNG DALAM PELAKSANAAN PENGELOLAAN KEUANGAN KAMPUNG KABUPATEN GAYO LUES - Sartika Ulandari; Syukriy Abdullah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The laws of Republic Indonesia No. 6 year 2014 concerning the Villages is a product of the reformation era that became initial form of village autonomy in governing nor managing the Village’s finance. Considering the funds received by the village is sufficiently a large number and keeps increasing every year, then in governing and managing village’s finance, it required for  reliable village apparatuses capacity and other appropriate fasilities in order to make the implementation more purposeful and more accountable. This study was conducted to provide empirically overview about the readiness of village apparatuses in implementating village finance in accountability in accordance to Law No. 6 of 2014 concerning the village. This research was conducted in eight villages in District of Gayo Lues, consists of, Jawa, Durin, Bacang, Bukit, Porang, Raklunung, Badak and Panglime Linting. This research is descriptive study which used qualitative data by conducted interview and documentation. The result shows that in eight villages  sampled, only one village were not ready in the planning process and accountability of village finance. The problem faced by village apparatuses in managing village’s finance is the lack of qualified human resources and have understanding about management of village’s finance, it results the village apparatuses prefer to use third parties services in preparing and formulating the reports required.